2019
DOI: 10.1007/978-3-030-19034-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Artifact-Facilitated Communication in Agile User-Centered Design

Abstract: One of the main challenges faced while establishing the integration of Agile and User-Centered Design is how to facilitate communication among the invariably distinct involved practitioners. Advocating the use of artifacts as enablers in this scenario, this paper aims to explore and understand the artifacts which can facilitate the communication between developers and designers in an Agile User-Centered Design approach. Drawing upon a netnography of a globally-distributed online community, we carried out commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
9
0
5
Order By: Relevance
“…Outra mudança significativa está relacionada a inserção do papel do Product Designer que impactou diretamente nas responsabilidade de todos os papéis, pois agora todos passam a desenvolver o produto centrado no usuário. Garcia, da Silva e Silveira [Garcia et al 2019] falam sobre a importância em ter uma pessoa que foca no usuário durante todo o processo de desenvolvimento do produto.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outra mudança significativa está relacionada a inserção do papel do Product Designer que impactou diretamente nas responsabilidade de todos os papéis, pois agora todos passam a desenvolver o produto centrado no usuário. Garcia, da Silva e Silveira [Garcia et al 2019] falam sobre a importância em ter uma pessoa que foca no usuário durante todo o processo de desenvolvimento do produto.…”
Section: Discussionunclassified
“…Como uma forma de promover melhorias nessa relação, estudos (e.g., [Dobrigkeit and de Paula 2017] ) têm relatado a necessidade de equipes adotarem uma abordagem combinada que utiliza User-Centered Design, Lean Startup eÁgil [Dobrigkeit and de Paula 2017]. A integração dessas três abordagens tem sido apontada como promissora uma vez que o User-Centered Design [Garcia et al 2019] fornece ao desenvolvimentoágil um roteiro para soluções criativas e centradas no usuário, enquanto o Lean Startup [Ries 2011] mantém os stakeholders envolvidos desde a concepção do produto, buscando rapidamente identificar as necessidades reais do usuário final e pivotando propostas de solução antes mesmo de iniciar o desenvolvimento de uma solução que possa vir a não ser a ideal ou necessária, focando no valor agregado ao negócio, fornece uma estrutura para validar e medir o ciclo de vida do produto.…”
Section: Introductionunclassified
“…According to these authors, artefacts support the introduction of a common language to avoid misunderstandings and misinterpretations. Garcia et al (2019) investigated an online agile community to understand how artefacts are used to mediate communication between UX and agile professionals. The results revealed that mock-ups, sketches of user interfaces and personas are the most used UX artefacts that support conversation in agile teams.…”
Section: Ux and Agilementioning
confidence: 99%
“…For example, several studies report that mockups are the artefact most often adopted by software professionals to represent UX work (Gray, 2016;Kashfi et al, 2017;Ardito et. al, 2014) and that mock-ups are used in combination with technical documents and user stories (Bordin and Angeli, 2016;Garcia et al, 2019). Others have also found that most UX information is discussed in agile ceremonies rather than captured in artefacts (Cajander et al, 2013;Garcia et al, 2019).…”
Section: Rq1 -Which Type Of Ux Information Do Agile Teams Process In Their Daily Work?mentioning
confidence: 99%
See 1 more Smart Citation